PECULARITIES OF TRANSITION OF YOUNG PEOPLE WITH DISABILITIES TO ADULT LIFE - Virbalienė, Rita; Baranauskienė, Ingrida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
During globalization process and development of technology the labor market is changing significantly and the demand for unskilled labor is decreasing. The integration of people with disabilities into society through such processes is even more complicated. The peculiarities of and risk factors and barriers to transition of young people with disabilities to adult life with specific attention to their career education and preparation for professional career presented by different researcher groups including Lithuanian examples are analyzed in the article. The critical review method and analysis of scientific literature are used.